2015
DOI: 10.1155/2015/916418
|View full text |Cite
|
Sign up to set email alerts
|

Research on Cloud Computing Resources Provisioning Based on Reinforcement Learning

Abstract: As one of the core issues for cloud computing, resource management adopts virtualization technology to shield the underlying resource heterogeneity and complexity which makes the massive distributed resources form a unified giant resource pool. It can achieve efficient resource provisioning by using the rational implementing resource management methods and techniques. Therefore, how to manage cloud computing resources effectively becomes a challenging research topic. By analyzing the executing progress of a us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…RL is a model-free learning method with powerful decision-making capability and can effectively solve multi-constrained MOO problem. Peng et al [12,13] utilized RL to find the optimal scheduling strategy and solve TSRA problem in cloud environments. Cui et al [14] proposed a task scheduling scheme based on RL, which also applies multi-agent and parallel technology to balance exploration and exploitation in the learning process, and achieves the maximum reduction of task makespan under the constraints of task deadlines and VM resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…RL is a model-free learning method with powerful decision-making capability and can effectively solve multi-constrained MOO problem. Peng et al [12,13] utilized RL to find the optimal scheduling strategy and solve TSRA problem in cloud environments. Cui et al [14] proposed a task scheduling scheme based on RL, which also applies multi-agent and parallel technology to balance exploration and exploitation in the learning process, and achieves the maximum reduction of task makespan under the constraints of task deadlines and VM resources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, we must specify the kernel size of a convolution kernel, it is often an odd number, and in most of the proposed CNN models, the kernel size is 3, 5, or 7. Since a larger size kernel often contains more parameters and we can get the same effect with a large kernel with multiple small kernels, we can just use the small kernels in the convolutional network [19].…”
Section: Deep Learning-related Technologiesmentioning
confidence: 99%
“…Previous works focusing on the performance of the MapReduce job have indicated the performance degradation in the virtual clusters [4][5][6][7]. Other researchers have found that the performance interference [8][9][10] is one of the important factors causing such degradation.…”
Section: Introductionmentioning
confidence: 99%